Apex scavengers from different European populations converge at threatened savannah landscapes - Delgado-González, A.; Cortés-Avizanda, A.; Serrano, D.; Arrondo, E.; Duriez, O.; Margalida, A.; Carrete, M.; Oliva-Vidal, P.; Sourp, E.; Morales-Reyes, Z.; García-Barón, I.; de la Riva, M.; et al. (Scientific reports, 2022)
Over millennia, human intervention has transformed European habitats mainly through extensive livestock grazing. “Dehesas/Montados” are an Iberian savannah-like ecosystem dominated by oak-trees, bushes and grass species that are subject to agricultural and extensive livestock uses. They are a good example of how large-scale, low intensive transformations can maintain high biodiversity levels as well as socio-economic and cultural values. However, the role that these human-modified habitats can play for individuals or species living beyond their borders is unknown. Here, using a dataset of 106 adult GPS-tagged Eurasian griffon vultures ( Gyps fulvus ) monitored over seven years, we show how individuals breeding in western European populations from Northern, Central, and Southern Spain, and Southern France made long-range forays (LRFs) of up to 800 km to converge in the threatened Iberian “dehesas” to forage. There, extensive livestock and wild ungulates provide large amounts of carcasses, which are available to scavengers from traditional exploitations and rewilding processes. Our results highlight that maintaining Iberian “dehesas” is critical not only for local biodiversity but also for long-term conservation and the ecosystem services provided by avian scavengers across the continent.